2013
DOI: 10.1063/1.4792697
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a true (t → 0+) quantum transition-state theory. I. Uniqueness and equivalence to ring-polymer molecular dynamics transition-state-theory

Abstract: Surprisingly, there exists a quantum flux-side time-correlation function which has a non-zero t → 0+ limit, and thus yields a rigorous quantum generalization of classical transition-state theory (TST). In this Part I of two articles, we introduce the new time-correlation function, and derive its t → 0+ limit. The new ingredient is a generalized Kubo transform which allows the flux and side dividing surfaces to be the same function of path-integral space. Choosing this common dividing surface to be a single poi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
219
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(225 citation statements)
references
References 60 publications
(176 reference statements)
5
219
0
1
Order By: Relevance
“…For example, for adiabatic dynamics, a dividing surface in nuclear-configuration space is usually defined and the TST assumption is that trajectories will never cross this dividing surface more than once. For the classical Born-Oppenheimer flux-side correlation function 55,56 and a particular generalization of its quantum equivalent, 53 it can be shown that the non-recrossing assumption leads to a step-like shape and therefore that the TST rate is proportional to its t → 0 + limit.…”
Section: A Quantum Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, for adiabatic dynamics, a dividing surface in nuclear-configuration space is usually defined and the TST assumption is that trajectories will never cross this dividing surface more than once. For the classical Born-Oppenheimer flux-side correlation function 55,56 and a particular generalization of its quantum equivalent, 53 it can be shown that the non-recrossing assumption leads to a step-like shape and therefore that the TST rate is proportional to its t → 0 + limit.…”
Section: A Quantum Formulationmentioning
confidence: 99%
“…V, the corresponding distribution will be localized about the crossing region. Like other quantum TSTs, 53 our formulation will not necessarily be variational, i.e. the exact rate may be smaller or larger than the TST rate.…”
Section: A Quantum Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Hele and Althorpe, 98 we transform to normal modes and do the integration over the N−1 delta functions…”
Section: Appendix B: Harmonic Limitmentioning
confidence: 99%